Case Report: A Case of Perifoveal Exudative Vascular Anomalous Complex With a Good Prognosis - Fu, Min; Hu, Pan; Zhang, Gang; Huang, Ludonghan; Xu, Huan; Huang, Ju; Wu, Meihui; Chen, Yanli (Frontiers in Medicine, 2021)
Significance: Perifoveal exudative vascular anomalous complex (PEVAC) is a unique clinical lesion. It manifests as isolated lesions and is easily misdiagnosed. Thus far, few PEVAC case reports have been published. PEVAC is typically inconsistent with other reported macular lesions. Purpose: To report our 24-month follow-up experience on the treatment of PEVAC with a micropulse laser (MPL). Case Report: A 56-year-old Chinese woman with no history of other diseases complained of decreased vision in her left eye that had persisted for more than 1 year. Comprehensive ophthalmic examinations were performed, including a vision test, slit lamp fundus exam, optical coherence tomography (OCT), optical coherence tomography angiography (OCT-A), fluorescein fundus angiography (FFA) and indocyanine green angiography (ICGA). Intravitreal injection of ranibizumab was ineffective, and bleeding, exudation and visual acuity were not improved. After two rounds of micropulse laser (MPL) treatment, the patient was followed up, and the prognosis was good. Conclusion: PEVAC is very rare, and early diagnosis is important, as the lesions readily cause irreversible damage. Our results indicate that an MPL can be used as an alternative treatment for PEVAC patients.